2001
DOI: 10.1073/pnas.011318098
|View full text |Cite
|
Sign up to set email alerts
|

PDK1 regulates growth through Akt and S6K in Drosophila

Abstract: The insulin͞insulin-like growth factor-1 signaling pathway promotes growth in invertebrates and vertebrates by increasing the levels of phosphatidylinositol 3,4,5-triphosphate through the activation of p110 phosphatidylinositol 3-kinase. Two key effectors of this pathway are the phosphoinositide-dependent protein kinase 1 (PDK1) and Akt͞PKB. Although genetic analysis in Caenorhabditis elegans has implicated Akt as the only relevant PDK1 substrate, cell culture studies have suggested that PDK1 has additional ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
130
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(145 citation statements)
references
References 41 publications
8
130
1
Order By: Relevance
“…The disparity between results reported here and those of Pekarsky et al (23) could indicate a cell type or transformation-state dependence on the outcome of TCL1 overexpression in regulating p70S6 kinase activity. Membrane-linked AKT has been shown to directly activate p70S6 kinase, whereas PDK1 phosphorylates p70S6 kinase when AKT is cytosol-restricted (42)(43)(44). Recently, we have shown that AKT and TCL1 interact optimally at the cytoplasmic membrane in transformed B cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…The disparity between results reported here and those of Pekarsky et al (23) could indicate a cell type or transformation-state dependence on the outcome of TCL1 overexpression in regulating p70S6 kinase activity. Membrane-linked AKT has been shown to directly activate p70S6 kinase, whereas PDK1 phosphorylates p70S6 kinase when AKT is cytosol-restricted (42)(43)(44). Recently, we have shown that AKT and TCL1 interact optimally at the cytoplasmic membrane in transformed B cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…Manipulation of virtually all components of the Drosophila insulin signaling pathway has been shown to alter organ and body size as a result of cell autonomous changes in cell size and number (reviewed in Stocker and Hafen, 2000;Weinkove and Leevers, 2000;Oldham and Hafen, 2003). For example, inactivation of positively acting molecules such as the insulin receptor, PI3K, chico (the insulin receptor substrate (IRS) ortholog), PDK1, Akt, TOR, Rheb, or S6K decreases organ and cell size concomitant with a slowing down of the cell cycle, while overexpression of many of these molecules increases organ and cell size (Bohni et al, 1999;Chen et al, 1996;Leevers et al, 1996;Montagne et al, 1999;Verdu et al, 1999;Oldham et al, 2000;Zhang et al, 2000;Rintelen et al, 2001;Saucedo et al, 2003;Stocker et al, 2003). Consistently, inactivation of negatively acting molecules such as PTEN or TSC1/2 increases organ and cell size, while their overexpression decreases organ and cell size (Gao et al, 2000;Goberdhan et al, 1999;Huang et al, 1999;Gao and Pan, 2001;Tapon et al, 2001a;Potter et al, 2002).…”
Section: Rheb An Activator Of Tor That Is Inhibited By Tsc2mentioning
confidence: 99%
“…In general, inactivation of genes that promote the insulin/PI3K/TOR pathway including Inr, IRS1-2/ Chico, PI3K/Dp110, PDK1, Akt, TOR, and S6K, reduces cell, organ or organism size; whereas activation of several of these genes has the opposite effect [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102]. Conversely, mutations in negative regulators of the pathway, such as PTEN, TSC1 or TSC2, increase cell or organ size; whereas overexpression of PTEN or both TSC1 and TSC2 causes reduced cell size or organ size ( Figure 2) [76,[103][104][105][106][107][108].…”
Section: Insulin/pi3-kinase/tor Pathwaymentioning
confidence: 99%